Antimicrobial activity of lactobacillus plantarum, isolated from local fermented food (tempe) / Nor Azila Abd Latif - Abd Latif, Nor Azila (2009)
Lactobacillus plantarum LS isolated from local fermented food has been shown to produce antimicrobial activity. Agar disk diffusion method was used in antimicrobial activity testing and inhibition zone around disk was measured and recorded. The antimicrobial compound from L. plantarum LS has been found to inhibit Staphylococcus aureus and Escherichia coli. This study demonstrated the presence of antibacterial compound showing a wider inhibitory spectrum that was produced during culture stationary phase. The growth profile of L. plantarum LS was also studied in shake flasks at temperature 37 °c and 100 rpm. Results indicated that mass production of this local isolated probiotic strain, L. plantarum LS had produced maximum cell concentration of 6.14 X 10¹¹ cfu/rnL at hour 20. Thus, L. plantarum LS can be useful as antimicrobial agent for many applications and further study of mass production of L. plantarum LS may assist many functional food industries to improve their yields and reduce their cost.